Collective Review: Current Approaches in German-Speaking Sociology of Architecture: Navigating Agency and Experience - Coughlan, Johannes; Wandelt, Alina (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2021)
Despite their differences, sociologists of architecture agree on one fundamental premise: buildings—and architecture more broadly—play a role in shaping social life. The importance of the "agency" of architecture has been equally highlighted in debates in cultural theory. The authors of the publications under discussion here approached this issue through empirical research. We suggest that, in doing so, they make visible the methodological challenges and potentials that confront sociologists of architecture. We aim to offer a comparative overview of some of the newer publications in the German-speaking sociology of architecture which adapt established methods of qualitative sociology to the field of architecture. We review these works through the lens of how well they empirically address the issue of the ways in which architecture can be shown to have agency in society.